1996
DOI: 10.1111/j.1476-5381.1996.tb15601.x
|View full text |Cite
|
Sign up to set email alerts
|

The site of anti‐arthritic action of the K‐opioid, U‐50,488H, in adjuvant arthritis: importance of local administration

Abstract: . Currently available pharmacological therapies treat arthritis inadequately. We have previously found that the kappa (K)‐opioid, U‐50,488H (trans‐(±)‐3,4‐dichloro‐N‐methyl‐N‐[2‐(1‐pyrrolidinyl) cyclohexyl]‐benzene‐acetamide methane sulphonate), possesses anti‐arthritic effects. In light of the finding that opioid receptors in the periphery are upregulated during inflammation, K‐opioids may represent a novel therapy for arthritis. The primary aim and unique feature of the present study is to investigate whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 35 publications
6
41
0
Order By: Relevance
“…The antagonist study confirmed that this local anti-nociception was in the tail and was mediated by different opioid receptors. These results support the notion that activation of peripheral opioid receptors can relieve nociception mediated by different mechanisms (Stein et al 1989;Stein 1995;Nagasaka et al 1996;Wilson et al 1996;Ko et al 1998Ko et al , 1999.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The antagonist study confirmed that this local anti-nociception was in the tail and was mediated by different opioid receptors. These results support the notion that activation of peripheral opioid receptors can relieve nociception mediated by different mechanisms (Stein et al 1989;Stein 1995;Nagasaka et al 1996;Wilson et al 1996;Ko et al 1998Ko et al , 1999.…”
Section: Discussionsupporting
confidence: 82%
“…More interestingly, when small, systemically inactive doses of mu or kappa opioid agonists were co-administered with capsaicin in the tail, they locally attenuated nociceptive responses (Ko et al 1998(Ko et al , 1999. These observations strengthen the notion that peripheral antinociception can be achieved by local administration of opioids into the injured tissue without producing central side effects (Stein 1995;Wilson et al 1996).…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Immune cells have been shown to contain and release opioid peptides, and immunosuppressive agents can inhibit these effects [1]. Upregulation of opioid receptors in the periphery during inflammation has been demonstrated [2]. However, the interaction between opioids and immune response is both complicated and significant [3].…”
Section: Introductionmentioning
confidence: 99%
“…Substantial evidence also described the peripheral mechanism of KOR agonists in mediating inflammation (238)(239)(240). KOR agonists have been proven previously as a powerful antiinflammatory therapy in a dose-dependent, time-dependent, stereo-selective and antagonist reversible manner during development of arthritis.…”
Section: Chronic Rhinosinusitis (Crs)mentioning
confidence: 99%